How does self-control influences college students’ smartphone dependence: The chain mediating effect of mental toughness and social adaptability - Quanwei Shen; Lin Li; Chenglong Li (PLoS ONE, 2026)
The study aimed to investigate the mediating roles of mental toughness and social adaptability in the relationship between self-control and smartphone dependence among college students. In January 2025, through a combination of convenience sampling and quota sampling methods, a total of 600 college students were selected from Hubei Province for a questionnaire survey. Mediation analysis was conducted with the SPSS PROCESS Model 6 to explore how mental toughness and social adaptability influence the connection between self-control and smartphone dependence. Results indicated that self-control, mental toughness, and social adaptability are all significantly negatively correlated with smartphone dependence. Self-control, mental toughness, and social adaptability show a positive correlation between each pair. Self-control can be associated with smartphone dependence through the path of social adaptability. mental toughness and social adaptability had a chain mediating relationship between self-control and smartphone dependence. The research results suggest that self-control ability is a key related factor for college students’ smartphone dependence. It is necessary for colleges and universities to enhance students’ beliefs and abilities to overcome and solve difficulties, enrich their extracurricular lives, help them better integrate into real society, and use smartphones reasonably.